A phase 2 study of simtuzumab in patients with primary, post‐polycythaemia vera or post‐essential thrombocythaemia myelofibrosis. (21st February 2017) - Verstovsek, Srdan; Savona, Michael R.; Mesa, Ruben A.; Dong, Hua; Maltzman, Julia D.; Sharma, Shringi; Silverman, Jeffrey; Oh, Stephen T.; Gotlib, Jason
Summary: Simtuzumab, a monoclonal antibody inhibitor of extracellular matrix enzyme lysyl oxidase‐like‐2, showed preclinical promise and was well tolerated in clinical studies. A phase 2, open‐label study of simtuzumab was conducted in patients with primary myelofibrosis (MF), post‐polycythaemia vera MF and post‐essential thrombocythaemia MF. Fifty‐four patients were randomized to receive simtuzumab alone (200 or 700 mg [ n  = 12 each group]) or simtuzumab (200 or 700 mg) with ruxolitinib ( n  = 15 each group) for 24 weeks. Simtuzumab alone or in combination with ruxolitinib showed no clinical benefit at 24 weeks. The mean serum simtuzumab trough concentrations appeared to increase dose‐proportionally between the 200‐mg and 700‐mg treatment groups. Therapy‐related serious adverse events were pyrexia, pain in extremity (both in 1 patient) and infusion reaction (in another patient). Bone marrow fibrosis (BMF) score was reduced at 24 weeks in 2 patients (16·7%) in the simtuzumab 700‐mg group, 1 (6·7%) in the simtuzumab 200‐mg + ruxolitinib group, and 2 (13·3%) in the simtuzumab 700‐mg + ruxolitinib group; similar numbers of patients had increased BMF. Simtuzumab alone or with ruxolitinib was well tolerated but did not produce clinical benefit nor consistently reduce BMF in patients with MF by 24 weeks.